Toward Pragmatic Realism in Human Geography - Rose, Courtice (Cahiers de géographie du Québec, 1990)
Classical realism describes the notion that the world we inhabit is completely mind-independent, that there is one unique account of the world and that truths about the world are a matter of the absolute correspondence between linguistic terms and their referents in the world. Human geographers have recently employed a form of transcendental realism inspired by the works of R. Bhaskar, A. Giddens and A. Sayer. This form of realism is anti-positivist and based on the dual notions of ontological stratification and emergent powers materialism. Reactions in geography have been both positive and negative indicating that neither classical realism, nor transcendental realism nor anti-realism seem acceptable. As a way of solving this dilemma, pragmatic (or internal) realism proposes the adoption of a natural ontological attitude toward the objects of geographical inquiry.